Rheumatoid arthritis related interstitial lung disease – improving outcomes over 25 years: a large multicentre UK study. (4th November 2020) - Kelly, Clive A; Nisar, Mohamed; Arthanari, Suba; Carty, Sarah; Woodhead, Felix A; Price-Forbes, Alex; Middleton, David; Dempsey, Owen; Miller, Dave; Basu, Neil; Dawson, Julie; Sathi, Nav; et al.
Abstract: Objective: This study explores whether the prognosis of interstitial lung disease in rheumatoid arthritis (RA-ILD) has improved over time and assesses the potential influence of drug therapy in a large multicentre UK network. Methods: We analysed data from 18 UK centres on patients meeting criteria for both RA and ILD diagnosed over a 25-year period. Data included age, disease duration, outcome and cause of death. We compared all cause and respiratory mortality between RA controls and RA-ILD patients, assessing the influence of specific drugs on mortality in four quartiles based on year of diagnosis. Results: A total of 290 RA-ILD patients were identified. All cause (respiratory) mortality was increased at 30% (18%) compared with controls 21% (7%) ( P =0.02). Overall, prognosis improved over quartiles with median age at death rising from 63 years to 78 years ( P =0.01). No effect on mortality was detected as a result of DMARD use in RA-ILD. Relative risk (RR) of death from any cause was increased among patients who had received anti-TNF therapy [2.09 (1.1–4.0)] P =0.03, while RR was lower in those treated with rituximab [0.52(0.1–2.1)] or mycophenolate [0.65 (0.2–2.0)]. Patients receiving rituximab as their first biologic had longer three (92%), five (82%) and seven year (80%) survival than those whose first biologic was an anti-TNF agent (82%, 76% and 64%, respectively) ( P =0.037). Discussion: This large retrospective multicentre study demonstrates survival of patients with RA-ILD has improved. This may relate to the increasing use of specific immunosuppressive and biologic agents.